2007
DOI: 10.1038/sj.jp.7211712
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological approaches to the management of pain in the neonatal intensive care unit

Abstract: Effective and consistent management of neonatal pain remains a controversial issue.Premature infants are repeatedly subjected to painful tests and procedures or suffer painful conditions when they are most vulnerable. With different mechanisms transducing various types of pain the practice of 'one-drug fits all' becomes questionable.Clinicians must use the latest non-pharmacologic and pharmacologic therapies for effective management of neonatal pain, distress, or agitation. Pharmacologic strategies for dealing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0
15

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(96 citation statements)
references
References 51 publications
1
80
0
15
Order By: Relevance
“…This is consistent with international standards for the adequate pain management of moderate to severe pain (Anand 2007;Lago et al 2009). Nursing studies addressing neonatal pain management support the implementation of non-pharmacological interventions, particularly with prevention and alleviation of neonatal procedural pain (Halimaa et al 2001;Spence et al 2010;Johnston et al 2010).…”
Section: Discussionsupporting
confidence: 64%
“…This is consistent with international standards for the adequate pain management of moderate to severe pain (Anand 2007;Lago et al 2009). Nursing studies addressing neonatal pain management support the implementation of non-pharmacological interventions, particularly with prevention and alleviation of neonatal procedural pain (Halimaa et al 2001;Spence et al 2010;Johnston et al 2010).…”
Section: Discussionsupporting
confidence: 64%
“…98 A systematic review in 2012 found insufficient evidence to recommend midazolam infusions for sedation in the NICU and raised safety concerns, particularly regarding neurotoxicity. 97 Alternative medications, such as methadone, 99 ketamine, propofol, and dexmedetomidine, have been proposed for pain management in neonates; however, few, if any, studies of these agents have been performed in this population, and caution should be exercised when considering them for use because of concerns about unanticipated adverse effects and potential neurotoxic effects. 100 Although the potential benefits of using methadone for the treatment of neonatal pain include satisfactory analgesic effects and enteral bioavailability as well as prolonged duration of action related to its long half-life and lower expense compared with other opiates, safe and effective dosing regimens have yet to be developed.…”
Section: Opioids Benzodiazepines and Other Drugsmentioning
confidence: 99%
“…Methadone was chosen as the opioid of choice because of its excellent oral bioavailability (70%-100%) and long half-life (19-41 hours), which allowed for long intervals between doses. 148 In this initial report, 3 symptomatic patients who had been exposed to continuous or bolus opioids for up to 7 weeks were transitioned to a methadone regimen of 0.1 mg/kg, orally, every 12 hours. Dose reduction by 10% to 20% of the initial dose per week resulted in successful weaning in 4 to 6 weeks.…”
Section: Management Of Acquired Opioid and Benzodiazepine Dependencymentioning
confidence: 99%